Visceral Adiposity and Neutralizing Antibody Expression: An Adult-Based Cross-Sectional Study - Wang H; Xiao D; Zhou H; Chen S; Xiao G; Hu J; Quan H; Luo M; Zhang S (Dove Medical Press, 2024)
Huanhuan Wang,1,* Dan Xiao,2,* Hua Zhou,3,* Shu Chen,4 Guangjun Xiao,4 Juan Hu,4 Hui Quan,2 Miao Luo,5 Shaocheng Zhang2,6 1School of Laboratory Medicine, Chengdu Medical College, Chengdu, Sichuan, People's Republic of China; 2Department of Laboratory Medicine, the Second Affiliated Hospital of Chengdu Medical College (Nuclear Industry 416 Hospital), Chengdu, Sichuan, People's Republic of China; 3Department of Laboratory Medicine, the Second Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 4Department of Laboratory Medicine, Suining Central Hospital, Suining, Sichuan, People's Republic of China; 5Department of Laboratory Medicine, the People's Hospital of Yubei District of Chongqing, Chongqing, People's Republic of China; 6School of Clinical Medicine, Chengdu Medical College, Chengdu, Sichuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Shaocheng Zhang; Miao Luo, Email 102024001@cmc.edu.cn; 536513878@qq.comPurpose: Visceral adiposity is a significant risk factor for severe COVID-19. However, the impact of the Chinese visceral adiposity index (CVAI) on the efficacy of SARS-CoV-2 vaccines remains poorly understood. This study aims to explore the impact of CVAI on the production of neutralizing antibodies (NAb) in inactivated SARS-CoV-2 vaccines and the potential mechanism, thereby optimizing vaccination guidance.Methods: In this cross-sectional study, 206 health workers (completed two SARS-CoV-2 vaccination on February 8th and March 10th, 2021, respectively) were recruited. All baseline anthropometric parameters of the participants were collected, and venous blood samples were obtained 6 weeks later to measure peripheral innate immune cells, inflammatory cytokines, and NAb titers against SARS-CoV-2. CVAI were calculated according to the formula and divided participants into two groups depending on CVAI median.Results: The median NAb titer among healthcare workers was 12.94 AU/mL, with an efficacy of 87.86% for the SARS-CoV-2 vaccine. NAb titers were lower in the CVAI dysfunction group than in the CVAI reference group (median: 11.40 AU/mL vs 15.57 AU/mL), the hsCRP levels (median: 0.50 mg/L vs 0.30 mg/L) and peripheral monocyte count (mean: 0.47 × 109/L vs 0.42 × 109/L) in the CVAI dysfunction group were higher than in the CVAI reference group. Additionally, CVAI showed positive correlations with hsCRP, monocytes, lymphocytes, and B-lymphocytes, and a negative correlation with NAb titers.Conclusion: CVAI may inhibit SARS-CoV-2 neutralizing antibody expression through inducing immune dysfunction and chronic inflammation. Thus, more attention should be paid to the vaccination for high CVAI population to improve the effectiveness of vaccination, which could provide more robust support for COVID-19 epidemic prevention and control.Keywords: Chinese visceral adiposity index, immune function, chronic inflammation, SARS-CoV-2 vaccine, neutralizing antibody